Parents’ Knowledge and Attitudes Toward Pediatric Ophthalmic Disorders in Saudi Arabia: A Cross-Sectional Study - Saja Radhi G. Alanazi; Haneen Wadi H. Alanazi; Wasan Ghathwan Alanazi; Nawal Surhuj Q. Alanazi; Dareen Owaid B. Alenezi; Maisa Al-Sweilem; Maram Hassan Alqattan; Iftikhar Lafi N. Alanazi; Jumanah Mohammed Tirksstani; Reem Saeed AlSarhan; Saleh Ghulaysi; Hanan A. Elgendy; et al. (Pediatric Reports)
Recognizing pediatric eye health issues at an early stage, along with ensuring that parents are well informed, is crucial. This study measures parents’ knowledge and perspectives on pediatric ophthalmic disease. The study utilized a cross-sectional design, and participants included Saudi parents of children residing in Saudi Arabia. Data were collected using a pre-validated self-administered questionnaire with a scoring system. Sociodemographic characteristics and factors associated with knowledge/attitude were collected and analyzed. Initially, 425 respondents participated in this study. Excluding the participants whose work was related to healthcare and those with incomplete data yielded 370 responses on which the subsequent analyses were performed. The analysis revealed that only half of the parents recognized the need for annual eye examinations for children. Most of them showed gaps in knowledge regarding the frequency of routine eye exams and indicators of visual problems. Notably, parents with good/excellent knowledge were more proactive in their eye care practices, such as adherence to recommended eye examination schedules and accepting corrective measures like glasses for common conditions such as refractive errors and amblyopia. However, parental willingness to permit surgical interventions did not correlate significantly with their level of knowledge, signaling the influence of other factors. In conclusion, this study underscores the need for enhanced public health education to improve parental awareness of pediatric eye diseases in Saudi Arabia. Given the link between knowledge and proactive eye health practices, targeted interventions should distribute comprehensive, culturally sensitive information accessible to all demographics.